Information sharing and collaboration applications to integrated biosurveillance : workshop summary - Patel, Deepali; Olson, Steve, 1956- (National Academies Press, 2012)
"After the September 11, 2001, terrorist attacks and subsequent anthrax mailings, the U.S. government prioritized a biosurveillance strategy aimed at detecting, monitoring, and characterizing national security health threats in human and animal populations, food, water, agriculture, and the environment. However, gaps and challenges in biosurveillance efforts and integration of biosurveillance activities remain. September 8-9, 2011, the IOM held a workshop to explore the information-sharing and collaboration processes needed for the nation's integrated biosurveillance strategy."-- Publisher's description.